Atrial stenting: case based elaboration of indications - Awasthy, Neeraj (Nepalese Heart Journal, 2020)
In certain forms of congenital and acquired heart defects, wide interatrial communication is important to maintain hemodynamics. In comparison to balloon septostomy or blade septostomy, atrial septal stenting provides a controlled, predictable, and longlasting atrial communication particularly in children and older age groups. Even though there are theoretical high risks of embolization, atrial stenting proves to be an effective palliative method. We describe 3 cases that underwent atrial stenting for different hemodynamic reasons. All three cases had different age groups. Two of them were moribund sick. Cases were performed under general anaesthesia with the help of transthoracic and transesophageal echo. Since it is uncommon procedure, we hope that this paper will the help in understanding clinical applications.